A taxonomical review on impact assessment of optimally placed DGs and FACTS controllers in power systems - Bindeshwar Singh; R. P. Payasi; Vipul Shukla (Energy Reports, 2017)
In the present scenario of all over the world like develops and undeveloped countries are fastly used Distributed Generations (DGs) and Flexible Alternating Current Transmission Systems (FACTS) controllers in power systems for reactive power supports so that the overall power system performances are improved such as minimization of real and reactive power losses, environmental pollutions and maximization of loadability of system, power system stability, the short circuit capacity of the line and also enhancement of voltage profile, available power transfer capacity of the system, reliability as well as security of the system and more flexible operations of the system. This survey paper presents a taxonomical review on impact assessment of DGs and FACTS controllers in power systems from different power system performance viewpoints and reveals the current status of research work in this field.
Keywords: 330; Artificial intelligence methods; Distribution Generations (DG); FACTS controllers; Flexible Alternating Current Transmission Systems (FACTS); Power flow analysis; Power system performances; Power systems